CRISPR‐Cas enzymes: The toolkit revolutionizing diagnostics. Issue 7 (23rd September 2021) - Verosloff, Matthew S.; Shapiro, Sarah J.; Hawkins, Elizabeth M.; Alpay, Emel; Verma, Deepika; Stanfield, Emma G.; Kreindler, Lior; Jain, Sonal; McKay, Bridget; Hubbell, Shae A.; Hendriks, Carley G.; Blizard, Benjamin A.; et al.
Abstract: The programmable nature of sequence‐specific targeting by CRISPR‐Cas nucleases has revolutionized a wide range of genomic applications and is now emerging as a method for nucleic acid detection. We explore how the diversity of CRISPR systems and their fundamental mechanisms have given rise to a wave of new methods for target recognition and readout. These cross‐disciplinary advances found at the intersection of CRISPR biology and engineering have led to the ability to rapidly generate solutions for emerging global challenges like the COVID‐19 pandemic. We further discuss the advances and potential for CRISPR‐based detection to have an impact across a continuum of diagnostic applications. Graphical Abstract and Lay Summary: The inherent programmability of CRISPR‐Cas nucleases has enabled new methods for molecular diagnostics. Powered by the intersection of CRISPR biology and engineering, CRISPR‐based diagnostics offer timely, accurate and actionable solutions across the continuum of testing applications.